Failure of Risk-Adjustment by Test Method for C. difficile Laboratory-Identified Event Reporting. (17th October 2016) - Marra, Alexandre R.; Edmond, Michael B.; Ford, Bradley A.; Herwaldt, Loreen A.; Algwizani, Abdullah R.; Diekema, Daniel J.
Abstract : Using an algorithm including both enzyme immunoassay (EIA) and nucleic acid amplification (NAAT) for Clostridium difficile infection (CDI) diagnosis, we found that the use of NAAT versus EIA almost doubled our hospital-onset CDI laboratory-identified (LabID) event standardized infection ratio (SIR). We recommend that the current risk adjustment approach be modified. Infect Control Hosp Epidemiol 2016:1–3